2019
DOI: 10.1186/s13058-019-1104-5
|View full text |Cite
|
Sign up to set email alerts
|

MiR-1287-5p inhibits triple negative breast cancer growth by interaction with phosphoinositide 3-kinase CB, thereby sensitizing cells for PI3Kinase inhibitors

Abstract: BackgroundNon-coding RNAs and especially microRNAs have been discovered to act as master regulators of cancer initiation and progression. The aim of our study was to discover and characterize the function of yet functionally uncharacterized microRNAs in human breast carcinogenesis.MethodsIn an unbiased approach, we utilized an established model system for breast cancer (BC) stem cell formation (“mammosphere assay”) to identify whole miRNome alterations in breast carcinogenesis. Clinical samples of BC patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 49 publications
3
48
0
Order By: Relevance
“…MiR-1287-5p has been revealed to play important roles in a variety of cancers including colorectal cancer, desmoids cancer, and breast cancer. For instance, a previous study has revealed the role of miR-1287-5p in triplenegative breast cancer through the regulation of phosphoinositide 3-kinase CB [25]. However, the roles of miR-1287-5p in the development of CHB are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-1287-5p has been revealed to play important roles in a variety of cancers including colorectal cancer, desmoids cancer, and breast cancer. For instance, a previous study has revealed the role of miR-1287-5p in triplenegative breast cancer through the regulation of phosphoinositide 3-kinase CB [25]. However, the roles of miR-1287-5p in the development of CHB are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging studies have confirmed that different miRNAs play diverse roles in TNBC, some as tumorigenic agents, and some as tumor inhibitors. For example, as tumorigenic agents, miR-25, 16 miR-20, 17 miR-224, 18 miR-135 19 and miR-301 20 promote the occurrence and development of TNBC, whereas miR-124, 15 miR-4417, 21 miR-4306, 22 miR-199, 23 miR-1287 24 and miR-3178 25 as tumor inhibitors inhibit the oncogenesis and development of TNBC. In this study, relative miR-153 expression in TNBC tissues and cells was remarkably lower than that in corresponding adjacent noncancerous tissues and normal breast epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…They were able to show that miR-1287-5p significantly decreased cellular growth, cells in S phase of cell cycle, anchorage-independent growth, and tumor formation in vivo. By identifying PI3Kinase pathway as a main regulated pathway, they also suggest a possible pharmacological link to miR-1287-5p [49]. Another example of the involvement of miRNAs in human cancer comes from a work published by Pichler and colleagues.…”
Section: Micrornas As Novel Emerging Biomarkersmentioning
confidence: 99%